PENGARUH LINGKUNGAN KERJA, PENGHARGAAN FINANSIAL DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA AKUNTANSI DALAM MEMILIH KARIR SEBAGAI AUDITOR (STUDI KASUS PADA MAHASISWA AKUNTANSI S1 UNIVERSITAS MUHAMMADIYAH JAKARTA) - Hendrawan, Agus; Lestari, Winda Maya Legisa (Taksasila Edukasi Insani, 2024)
ABSTRACTThis research aims to determine whether there is an influence between the work environment, financial rewards and job market considerations on accounting students' interest in choosing a career as an auditor. This research is included in the type of quantitative research. The population in this study were undergraduate accounting students class 2019-2020 at the Faculty of Economics and Business, Muhammadiyah University, Jakarta. Determining the number of samples from the population in this study used the Slovin formula which resulted in 69 respondents determined using a purposive sampling technique. The analysis technique uses Structural Equation Modeling (SEM) statistics with a Partial Least Square (PLS) approach with the help of the SmartPLS 0.4 for Windows application.The research results show that the work environment has a negative and insignificant effect on accounting students' interest in choosing a career as an auditor, financial rewards have a positive and insignificant effect on accounting students' interest in choosing a career as an auditor, job market considerations have a positive and significant effect on accounting students' interest in choosing a career as an auditor and the work environment, financial rewards, and job market considerations simultaneously have a positive and significant effect on accounting students' interest in choosing a career as an auditor. Keywords : Work Environment, Financial Rewards, Job Market Considerations,Interests Choosing a Career as an Auditor